Pengaruh Karakteristik CEO terhadap Manajemen Laba : (Studi Empiris Perusahaan Subsektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia) - Ghaisani Putri ZM; Retno Yuni Nur Susilowati (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2025)
Earnings management is an action that can affect the quality of a company's financial information. As the highest leader, the CEO plays a critical role in strategic decision-making, including in earnings management practices. This study aims to examine the influence of CEO characteristics—namely age, education level, and tenure—on earnings management in food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the 2019–2023 period. A quantitative approach is employed using secondary data from annual reports of 21 companies, with a total of 99 firm-year observations. The data were analyzed using multiple linear regression with leverage, profitability, and sales growth as control variables. The results show that CEO age has a negative effect on earnings management, CEO tenure has a positive effect, while CEO education level shows no significant effect. These findings indicate that the personal characteristics of CEOs influence a company’s tendency to engage in earnings management. This study provides insights for investors, management, and regulators to consider CEO attributes when assessing the risk of financial reporting manipulation.